Quantum mechanics simulation of Cadmium(II) tripeptide complexes - Abdalla, Shaho Mohammed (2017)
Cadmium detection in aqueous medium is an important step in attempt to avoid human exposure to the extremely toxic metal. It is believed that one of the significant qualitative detection processes of cadmium(II) can be performed using a biosensor with the help of small peptides as the biological material. The current issue is that proper peptides to capture cadmium(II) are still unknown, since there is not enough information about the interaction between the metal ion and most of the small peptides in literature. Quantum mechanics methods, such as Density Functional Theory (DFT), can be employed to understand the electronic interaction between cadmium(II) and the peptides. Minnesota 06 functional (M06) in combination with Default 2 triple zeta plus polarization (Def2TZVP) basis set was denoted as the best method among those, which were employed in this research to describe properties of several cadmium complexes, such as Cd-S bond length and S-Cd-S bond angle. For this purpose, data on cadmium(II) benzenthiolato was extracted from Cambridge Structural Database (CSD) and compared to the computed data on the same molecule achieved theoretically using Becke Three Parameter Hybrid Functional in combination with Double zeta split-valence plus polarization basis set (B3LYP/DGDZVP) and M06/Def2TZVP. The results from the second method yielded 2.66% of errors for Cd-S bond lengths and 2.87% of errors for S-Cd-S bond angles, while in the presence of DGDZVP basis set in combination with B3LYP the errors rose up to 5.17% in Cd-S bond lengths and 4.90% in S-Cd-S bond angles. Cadmium(II) complexes with the small peptides, such as dipeptide, tripeptide and tetrapeptide were optimized employing M06/Def2TZVP and Polarizable Continuum Method (PCM) to determine the peptide length effect on the Cd-Sbinding energy. Cd-S binding energy in the tripeptide, if compared with the dipeptide and the tetrapeptide, was bigger as much as 12.62 kJ and 5.82 kJ respectively. Therefore, Cd-S binding energy of different tripeptide sequences were screened by fixing cysteine in the terminals and changing the middle amino acid to each one of the twenty essential amino acids. The optimization was performed in vacuum using B3LYP/DGDZVP and M06/Def2TZVP methods. The procedures were repeated using PCM, in which water was chosen as the solvent, to investigate dielectric effect of water molecules on the Cd-S moiety. Cd-S binding energy of Cysteine-Proline-Cysteine (CPC) is the highest, if compared to the other observed nineteen tripeptides with the binding energies of 285.98 kJ in the presence of PCM using M06/Def2TZVP. The computed bond lengths between the metal ion and the sulfur atoms, using M06/Def2TZVP, are between 2.353 Å to 2.476 Å in vacuum, and 2.434 Å to 2.451 Å with PCM. Thus, CPC peptide could serve as biological material in the cadmium(II) biosensor application.